Linezolid resistance in patients with drug-resistant TB and treatment failure in South Africa. (12th May 2019) - Wasserman, Sean; Louw, Gail; Ramangoaela, Limpho; Barber, Garrick; Hayes, Cindy; Omar, Shaheed Vally; Maartens, Gary; Barry, Clifton; Song, Taeksun; Meintjes, Graeme
Abstract: Objectives: Limited data exist on clinical associations and genotypic correlates of linezolid resistance in Mycobacterium tuberculosis . We aimed to describe mutations and clinical factors associated with phenotypic linezolid resistance from patients with drug-resistant TB at two public sector facilities in South Africa. Methods: Adults and adolescents with treatment failure (culture positivity ≥4 months) on a linezolid-containing regimen were retrospectively identified. Phenotypic resistance, as defined by a linezolid MIC >1 mg/L, was assessed for retrieved isolates using broth microdilution. Targeted sequencing of rrl and rplC was performed, irrespective of growth on subculture. Results: Thirty-nine patients with linezolid-based treatment failure were identified, 13 (33%) of whom had phenotypic or genotypic linezolid resistance after a median duration of 22 months (range = 7–32) of linezolid therapy. Paired MIC testing and genotyping was performed on 55 unique isolates. All isolates with phenotypic resistance ( n  = 16) were associated with known resistance mutations, most frequently due to the T460C substitution in rplC ( n  = 10); rrl mutations included G2814T, G2270C/T and A2810C. No mutations were detected in isolates with MICs at or below the critical concentration. Conclusions: Linezolid resistance occurred in a third of patients with drug-resistant TB and treatment failure. Resistance occurred late and was predicted by a limited number of mutations in rrl and rplC . Screening for genotypic resistance should be considered for patients with a positive culture after 4 months of linezolid therapy in order to optimize treatment and avoid the toxicity of ineffective linezolid therapy.